Modified Constitutive Relation Error for Multi-Physics Wind Turbine Calibration. Issue 4 (1st May 2022) - Roussel, A.; Capaldo, M.; Chamoin, L.; Argaud, J.-P.
Abstract: Asbtract. Despite the availability of massive operation datasets, numerous uncertain parameters linger in offshore wind modeling. We propose an identification procedure based on reliability of information coming from both modeling and measurements. The procedure is constructed from the modified Constitutive Relation Error concept, which considers measurement noise and model uncertainties. This concept is extended to a multi-physics context involving nonlinear fluid-structure interactions. Several constitutive laws are assumed unreliable and relaxed for comparison with data and safe identification.